Reduction of the field‐aligned potential drop in the polar cap during large geomagnetic storms. Issue 8 (2nd August 2013) - Kitamura, N.; Seki, K.; Nishimura, Y.; Hori, T.; Terada, N.; Ono, T.; Strangeway, R. J.
Abstract: [1] We have studied photoelectron flows and the inferred field‐aligned potential drop in the polar cap during five large geomagnetic storms, which occurred in the periods when the photoelectron observations in the polar cap are available near the apogee of the Fast Auroral SnapshoT satellite ( 4000 km) at solar maximum, and the footprint of the satellite paths in the polar cap was under sunlit conditions most of the time. In contrast to the 20 V potential drop during geomagnetically quiet periods at solar maximum identified by Kitamura et al. (2012), the field‐aligned potential drop frequently became smaller than 5 V during the main and early recovery phases of the large geomagnetic storms. This result indicates that the acceleration of ions by a field‐aligned potential drop in the polar cap and the lobe region is smaller during the main and early recovery phases of large geomagnetic storms compared to during geomagnetically quiet periods. Since ions with large flux originating from the cusp/cleft ionosphere convect into the polar cap during geomagnetic storms, the net escaping electron number flux should increase to balance the enhanced ion outflows under small field‐aligned current conditions. The magnitude of the field‐aligned potential drop would be reduced to let larger part of photoelectrons escape. Key Points: Precipitating reflected photoelectrons dissappered in the polar cap The disappearance corresponds to the period of a large southward IMF The disappearance indicates a reduction of the field‐aligned potential drop